A case study on management styles of managing family business in selected restaurants in Iloilo City - Abraham, Ma. Aurora
This study was conducted to know what Filipino management style is being used by Ilonggo entrepreneurs in managing their family owned business. This study aims to meet the following objectives: 1) To identify if Filipino managers use the realist style of management in managing their family business. 2) To find out if Filipino manager aplly the idealsit sytle of management in managing their family business. 3) To determine if Filipino managers employ the opportunist style of management in managing their family business. 4) To identify if Filipino managers utilize the reconciler style of management in managing their family business. An interview was conducted to the three owner-managers of selected restaurants in Iloilo city. These restaurants are Afriques, Mundo and Breakthrough. A survey sheet containing the different characteristics was also given. This study uses a descriptive method of research and the data gathered were treated statistically through percentages and frequency counts. Considering all the finding, the Reconciler Management Style is the most dominantly applied by the family members in managing their own business.